PERANCANGAN SISTEM INFORMASI SUMBER DAYA MANUSIA PADA PT. HANDAREN SUBUR SEJAHTERA - Lauren, Cornelius Ernest; Dasawati, Elis Sondang (Jurnal Informatika dan Bisnis, 2022)
PT. Handaren Subur Sejahtera is a company that owns and uses many applications in carrying out operational activities. However, in practice, the company does not yet have a system for calculating extra working hours for overtime incentives and calculating absenteeism. This research will be conducted using the waterfall software development method, which is a system development method that has a sequential nature so that it makes this type of development model very easy to group, manage, and monitor at each stage. Data collection is done by direct observation, interviews with those who provide information in the company and literature studies from books and journals that are used as references on human resources. The design of this system will be done by designing the system architecture, use cases and activity diagrams to describe the program in detail. This research was also made using information and constraints that were obtained and collected from the company. The results of the design that has been made in the form of a web application. Keywords: Human Resource Information System, Waterfall Model